PENGARUH PENGGUNAAN MEDIA PEMBELAJARAN BERBASIS PROBLEM-BASED LEARNING TERHADAP MINAT BELAJAR SISWA PADA MATERI SISTEM PEMBAYARAN DAN ALAT PEMBAYARAN - Munthe, Raja Parnaungan; Evi Syuriani Harahap; Erikson Sinaga; Gresia Apriyani; Sri Ramadhani Siregar (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Low student interest in learning economics has become the underlying phenomenon behind this study. In an effort to address this issue, the research focuses on examining the effectiveness of implementing the Problem-Based Learning (PBL) model as the basis for developing learning media, particularly in the context of the topics of payment systems and payment instruments. Methodologically, this study adopts a quantitative approach with a descriptive design. Data collection was carried out through the distribution of questionnaires consisting of 30 Likert-scale statement items to 32 respondents. The quality of the instrument was tested through two stages: a validity test, which showed that all items met the required criteria with correlation coefficients ranging from 0.444 to 0.821, and a reliability test, which produced a Cronbach’s Alpha value of 0.956, indicating excellent instrument consistency. The assumption of normality was confirmed through the Kolmogorov-Smirnov test, which yielded a significance value of 0.079 > 0.05. Based on the analysis conducted, it was found that the integration of PBL-based learning media was significantly associated with an increase in students’ learning interest. The problem-based approach proved effective in encouraging active participation, fostering analytical thinking patterns, and enhancing students’ enthusiasm for learning in understanding concepts related to payment systems and payment instruments.